Analisis Yuridis Pembentukan Undang-Undang Cipta Kerja Menurut Teori Perundang-Undangan - Subowo, Adi; Ismono, Joko (Law and Humanity, 2024)
The principles that make up laws and regulations, both formal and material, are usually ignored when making the Job Creation Law. The focus of this research is whether the Job Creation Law is in accordance with being carried out transparently and whether the legislative process of the Job Creation Law is considered too fast and ignores democratic principles. Normative juridical legal research, or research on legal standards, is used as a research methodology. Secondary data are obtained by combining data from primary, secondary, and tertiary legal materials. The results showed that Law Number 11 of 2020 concerning Job Creation has no legal force at the drafting stage, violating the NRI Constitution of 1945 and the principles of Law Number 12 of 2011 as amended by Law Number 15 of 2019 concerning the Establishment of Laws and Regulations. Adolf Merkel's double-faced theory and Hans Nawiasky's level theory meet the Job Creation Law. Here, the highest standards are Pancasila and the Indonesian Constitution of 1945, which are the basic standards of the country. According to Hans Nawiasky's theory, the Job Creation Law is considered a formal, gesetz, or formal law.